2020
DOI: 10.1002/jcla.23296
|View full text |Cite
|
Sign up to set email alerts
|

Ion chromatography as candidate reference method for the determination of chloride in human serum

Abstract: Background We developed an ion chromatography (IC) method for measurement of chloride in human serum which was regarded as a simple, rapid, accurate, and sensitive technique. The method will be hopefully selected as a candidate reference method. Method Serum aliquots of 0.1 mL were diluted 500 times with Milli‐Q water, and chloride in serum samples was measured by IC with a gradient elution procedure using a KOH eluent generator. Results Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In this study, normal chloride levels were defined as 98 to 106 mEq/L [ 20 ]. However, a precise definition of acidosis or acidemia is lacking; we found definitions of childhood metabolic acidosis as a pH < 7.35, HCO 3 − level < 22 mEq/L, or base excess ≤ 5 mmol/L [ 11 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, normal chloride levels were defined as 98 to 106 mEq/L [ 20 ]. However, a precise definition of acidosis or acidemia is lacking; we found definitions of childhood metabolic acidosis as a pH < 7.35, HCO 3 − level < 22 mEq/L, or base excess ≤ 5 mmol/L [ 11 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…LGC ERM-DA253a (frozen human serum) fulfil APS for the total MU budget on clinical samples regardless of the higher-order reference selected. To this regard, it would be interesting to determine whether the use of a RMP based on the ion chromatography principle may significantly improve the associated MU and permit the MU for chloride to get close to the APS as already observed for other plasma/serum ions (35,36).…”
Section: Resultsmentioning
confidence: 96%
“…Using the peak area and the standard curve, the concentration of the target ion is calculated. Many studies have shown that IC accurately determines Cl − ions in serum and sweat samples (2,7), and it has been recommended as a candidate reference method for the determination of Cl − in human serum (2). In this case, we assumed that the 112 mmol/L Cl − concentration was more accurate than the 130 mmol/L concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The Cl − level can be measured by numerous methods (2), such as the inductively coupled plasma mass spectrometry method, the ion chromatography (IC) method, the ion selective electrode (ISE) method, and the enzyme coupling method. IC is recommended as a candidate reference method because it is a simple, rapid, accurate, and sensitive technique (2). In relation to cost and convenience, the ISE method is the most common method used to determine the serum Cllevel in many hospitals.…”
Section: Introductionmentioning
confidence: 99%